Die (Un)möglichkeit des Seins in Sally Perels Autobiografie Ich war Hitlerjunge Salomon - Habib Tekin (Moderna Språk)
Sally Perel is a German-Jewish author and Holocaust survivor. During WW2, he tried to protect himself by camouflaging as an ‘Arian’ member of the Hitler Youth, thereby leading a double life as a perpetrator and victim in one person. In Perel, these two identities got along like fire and water and were still present in the same body.